Response, Effectiveness and Accuracy of Different Selection Methods and Intensities In Dairy Cattle - Santosa, SA; Sudewo, ATA; Susanto, A; Iswoyo, Iswoyo (ANIMAL PRODUCTION, 2009)
A data set of dairy cattle production and reproduction taken from Baturraden Dairy Cattle Breeding Centre (Balai Besar Pembibitan Ternak Unggul; BBPTU) was used in the study.  The data included were 180 records of milk production collected from first, second and third lactation.  The  objectives of the study were : (1) to estimate heritability and repeatability of the milk production, (2) to compute accuracy, response and effectiveness of individual selection on different selection methods and intensities, (3) to study the best lactation period for selection in dairy cattle. Some conclusion can be drawn: (1) the estimated repeatability of milk production was considered low, the opposite was true for heritability estimate, (2) the selection response and its effectiveness increased when the number of animals maintained in the population decreased, (3) the selection accuracy increased along with the increased of number of record included, (4) the highest selection accuracy was obtained from individual selection with three records whilst the family selection resulted in the lowest selection accuracy.  It was also concluded that selection in dairy cattle can be done as early as the first lactation and the accuracy will be increased if combined with the information from relatives. (Animal Production 11(1): 66-70 (2009) Key Words:  dairy cattle, effectiveness selection method